Factors associated with dental health care coverage in Mexico: findings from the National Performance Evaluation Survey 2002–2003 - Pe´rez-Nu´n˜ez R, Medina-Solis CE, Maupome´ G, Vargas-Palacios A. (Blackwell Synergy, 2006)
To determine the level of dental health care coverage in people aged ‡18 years across the country, and to identify the factors associated with coverage.